Implementasi Manajemen Pendidikan Multikultural di SMP Tumbuh Yogyakarta - Nurcholish, Dani (Pendidikan Agama Islam, 2019)
This article wants to explain about the application of multicultural education management in SMP Tumbuh Yogyakarta. With the vision of the school